Desarrollo de una metodología para la coordinación de aislamiento en redes eléctricas de media tensión. - Escarabay Bastidas, Hernán Stéfano. (2016)
The present research work describes the methodological development for the coordination of the insulation of electrical medium voltage network, the developed methodology consists on procedures of calculation which are evaluated the different factors that are involved in order to define and dimensioning the proper insulation level for the equipment that form a primary network. To apply this methodology it is convenient to know and determine the system’s operating parameters in studying and the determination of the different components of it. So through the appropriate procedures can define the electrical characteristics that should get the downloader (lightning rod) and according to the rules CEI 60071-1 Y CEI 60071-2 determining the types and levels of the over tensions that could occur on the network, taken into account the different factors of coordination, safety and correction by height, all of them are necessary in order to cover the possible defects that could carry out in the insulation due to the real conditions of the operation and then select an appropriate insulation level. To get the validity of the developed methodology was taken as reference the parameters of operation which are in the “Alimentador Primario Villonaco”. It is important to mention that through the application of the performed process was possible to have favorable results which reflect and determine the effectiveness of the present research work and verified the appropriate design that has the selected circuit for the study.